Metadata integration in electronic records management systems: a comparative study of international best practices - Hussin, Nurussobah; Ismail, Azratul Ain Nadiah; Mustakin, Nur Imana; Daud, Roslaizam; Bunawan, Ap Azli; Ahmad, Mohd Nazir (Faculty of Information Management, 2025)
Metadata plays a critical role in ensuring the authenticity, reliability, and accessibility of electronic records. This study proposes a unified metadata framework for Electronic Records Management Systems (ERMS) by analysing three prominent standards: ISO 23081-1:2017, the Minimum Recordkeeping Metadata Requirements (State Records Act 1997), and the Recordkeeping Metadata Standard (East Renfrewshire Council). A qualitative comparative analysis highlights structural, contextual, and content-and-use metadata elements essential for record creation, classification, maintenance, retention, and disposition. To enhance transparency, an explicit analytical framework was applied to guide the evaluation and ensure validity of findings. The proposed framework integrates best practices to address compliance, system interoperability, and digital preservation. The study concludes with actionable recommendations to support sustainable metadata management in evolving digital environments.